The Origin of Language and Consciousness How Social Orders and Communicative Concerns Gave Rise to Speech and Cognitive Abilities - Rozov, Nikolai S. (World-Systems Evolution and Global Futures, 2023)
XLIX, 361 p. 68 illus.